2020
DOI: 10.5802/crphys.17
|View full text |Cite
|
Sign up to set email alerts
|

Fluid dynamics of a mixed convective/stably stratified system—A review of some recent works

Abstract: Fluid dynamics of a mixed convective/stably stratified system-A review of some recent works Dynamique des fluides d'un système mixte convectif / stablement stratifié -Une revue de quelques travaux récents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Buffett and Knezek (2018) investigated linear excitation and found that Maxwell stresses yield an efficient generation mechanism with most power in the period range 30 to 100 years, long compared to the timescales discussed here. We may learn also from other fluid systems where a stratified layer is adjacent to a turbulent layer such as the Earth's stratosphere or the Sun's tachocline (Le Bars et al 2020). The quasi-biennial oscillation of the Earth's atmosphere has been much studied.…”
Section: Mac Waves In a Stratified Layermentioning
confidence: 99%
“…Buffett and Knezek (2018) investigated linear excitation and found that Maxwell stresses yield an efficient generation mechanism with most power in the period range 30 to 100 years, long compared to the timescales discussed here. We may learn also from other fluid systems where a stratified layer is adjacent to a turbulent layer such as the Earth's stratosphere or the Sun's tachocline (Le Bars et al 2020). The quasi-biennial oscillation of the Earth's atmosphere has been much studied.…”
Section: Mac Waves In a Stratified Layermentioning
confidence: 99%